Transport at high βp and development of candidate steady state scenarios for ITER. (11th March 2020) - McClenaghan, J.; Garofalo, A.M.; Lao, L.L.; Weisberg, D.B.; Meneghini, O.; Smith, S.P.; Lyons, B.C.; Staebler, G.M.; Ding, S.Y.; Huang, J.; Gong, X.; Qian, J.; et al.
Abstract: On DIII-D, the high scenario has an internal transport barrier (ITB), , , and very high normalized confinement . Recently, plasmas starting with these conditions have been dynamically driven to and, where we find the ITB and high performance persist for five energy confinement times. These conditions are projected to meet the ITER steady-state goal of Q   =  5. The ITB is maintained at lower with a strong reverse shear, consistent with predictions that negative central shear can lower the threshold for the ITB. There are two observed confinement states in the high scenario: H-mode confinement state with a high edge pedestal, and an enhanced confinement state with a low pedestal and an ITB. It has been observed in a scan of external resonant magnetic perturbation amplitude that when there are no large type-I ELMs, there is no transition to enhanced confinement. This is consistent with the proposed mechanism for ITB formation being a type-I ELM. Quasilinear gyro-Landau fluid predictive modeling of ITER suggests that only a modest reverse shear is required to achieve the ITB formation necessary for Q   =  5 when electromagnetic physics including the kinetic ballooning mode (KBM) is incorporated.